Usefulness of Accounting Theory and Practices on Large Business Organizations in Nigeria - Augustine E., Osho,; Akinwumi O., Akinola, (European Scientific Journal, ESJ, 2018)
The study was about the impact of accounting theory and practice on performance of large scale business in Nigeria. The objective of the study was to examine the effect and usefulness of accounting theory and practice on financial performance of large firms. The research was carried out, using Coscharis Group Limited as the case study. Primary Data was collected through simple random sampling and using self-administered questionnaires for 20 respondents. Secondary Data was gotten from the company’s annual reports on return on equity for the period 2014-2016. The primary and secondary data were consolidated for analysis. Multiple Linear Regression was used to analyze the data to test for the relationship between the accounting theory and practice variables (Positive Accounting Theory(PAT), Financial Reporting(FR), Auditing Practice (AP) and Budgeting) and Financial Performance(Return on Equity). Findings revealed that accounting theory and practice have significant relationship with the financial performance of large companies in Nigeria. It further shows that variables of accounting practice have significant effect on financial performance of large firms in Nigeria. It is recommended that quoted and unquoted organizations should ensure there is consistency in the accounting theory and practice adopted in preparation of their records to enhance stability in their financial performance.